Augmented reality navigation in open surgery for hilar cholangiocarcinoma resection with hemihepatectomy using video-based in situ three-dimensional anatomical modeling: A case report. Issue 37 (September 2017) - Tang, Rui; Ma, Longfei; Xiang, Canhong; Wang, Xuedong; Li, Ang; Liao, Hongen; Dong, Jiahong
Abstract: Rationale: Patients who undergo hilar cholangiocarcinoma (HCAC) resection with concomitant hepatectomy have a high risk of postoperative morbidity and mortality due to surgical trauma to the hepatic and biliary vasculature. Patient concerns: A 58-year-old Chinese man with yellowing skin and sclera, abdominal distension, pruritus, and anorexia for approximately 3 weeks. Diagnoses: Magnetic resonance cholangiopancreatography and enhanced computed tomography (CT) scanning revealed a mass over the biliary tree at the porta hepatis, which diagnosed to be s a hilar cholangiocarcinoma. Intervention: Three-dimensional (3D) images of the patient's hepatic and biliary structures were reconstructed preoperatively from CT data, and the 3D images were used for preoperative planning and augmented reality (AR)-assisted intraoperative navigation during open HCAC resection with hemihepatectomy. A 3D-printed model of the patient's biliary structures was also used intraoperatively as a visual reference. Outcomes: No serious postoperative complications occurred, and the patient was tumor-free at the 9-month follow-up examination based on CT results. Lessons: AR-assisted preoperative planning and intraoperative navigation might be beneficial in other patients with HCAC patients to reduce postoperative complications and ensure disease-free survival. In our postoperative analysis, we also found that, when the3D images were superimposed 3D-printed model using a see-through integral video graphy display device, our senses of depth perception and motion parallax were improved, compared with that which we had experienced intraoperatively using the videobased AR display system.